Virtual patients as the basis for problem-based learning of cardiologists - S. I. Karas; M. B. Arzhanik; E. E. Kara-Sal; E. V. Grakova; O. Y. Vasiltseva; W. Y. Ussov; V. Kh. Vaizov; K. V. Zavadovsky; V. M. Gulyaev; A. E. Baev; S. O. Kolganov; S. B. Kochetkov; et al. (Бюллетень сибирской медицины, 2021)
Implementation of virtual patients allows avoiding risks for patient safety, using the standardized clinical situations repeatedly, and providing remote access to information. In order to create virtual patients, the project team comprised of specialists competent in the diverse subject areas. Every virtual patient is a structural model for a diagnostic and treatment process of a real patient augmented with textual and multimedia information. A sample comprising of 50 archival clinical charts of patients with typical cardiovascular diseases and rare pathology variants was formed. Textual information from medical records is supplemented with the multimedia results of instrumental and laboratory studies. Created data and knowledge base of virtual patients was designated for a demonstration of complete cardiovascular cases to the trainees in linear trajectory with an option of Web-access. The virtual patient repository will become a factual basis for problem-based distance learning of medical students and physicians.